500 days of SN 2013dy: spectra and photometry from the ultraviolet to the infrared - Pan, Y. C. (2015)
SN 2013dy is a Type Ia supernova (SN Ia) for which we have compiled an extraordinary data set spanning from 0.1 to ∼ 500 d after explosion. We present 10 epochs of ultraviolet (UV) through near-infrared (NIR) spectra with Hubble Space Telescope/Space Telescope Imaging Spectrograph, 47 epochs of optical spectra (15 of them having high resolution), and more than 500 photometric observations in the BVrRiIZYJH bands. SN 2013dy has a broad and slowly declining light curve (Δm15(B) = 0.92 mag), shallow Si II λ 6355 absorption, and a low velocity gradient. We detect strong C II in our earliest spectra, probing unburned progenitor material in the outermost layers of the SN ejecta, but this feature fades within a few days. The UV continuum of SN 2013dy, which is strongly affected by the metal abundance of the progenitor star, suggests that SN 2013dy had a relatively high-metallicity progenitor. Examining one of the largest single set of high-resolution spectra for an SN Ia, we find no evidence of variable absorption from circumstellar material. Combining our UV spectra, NIR photometry, and high-cadence optical photometry, we construct a bolometric light curve, showing that SN 2013dy had a maximum luminosity of 10.0+4.8-3.8 × 1042 erg s-1. We compare the synthetic light curves and spectra of several models to SN 2013dy, finding that SN 2013dy is in good agreement with a solar-metallicity W7 model.